PEMBERDAYAAN REMAJA MELALUI PROGRAM DAKWAH DAN PENDIDIKAN DPD BKPRMI KOTA MEDAN : PEMBERDAYAAN REMAJA MELALUI PROGRAM DAKWAH DAN PENDIDIKAN DPD BKPRMI KOTA MEDAN - Suci Ramadayani; Abdullah Abdullah (Communicative : Jurnal Komunikasi dan Penyiaran Islam, 2026)
This study examines the empowerment of adolescents through da'wah and educational programs organized by the Regional Executive Board (DPD) of the Indonesian Mosque Youth Communication Body (BKPRMI) in Medan City. The research was motivated by declining adolescent involvement in mosque-based activities alongside the growing prevalence of social problems among youth, including delinquency and inter-group conflict. Employing a qualitative descriptive design, data were gathered through in-depth interviews, observation, and documentation, then analyzed using the interactive model of data reduction, display, and conclusion drawing developed by Miles and Huberman (1984). Findings indicate that the programs strengthened adolescent participation, cultivated practical and leadership skills, and fostered disciplined, socially responsible character. Da'wah activities, skills training, and community service formed the core of the intervention. Despite constraints such as limited time and uneven motivation, sustained managerial effort combined with government and community support enabled the program to function as a promising model for mosque-based youth development across Indonesia.